2021
DOI: 10.1212/cpj.0000000000001047
|View full text |Cite
|
Sign up to set email alerts
|

Ganglionic Acetylcholine Receptor Antibodies in Postural Tachycardia Syndrome

Abstract: ObjectivePostural tachycardia syndrome (POTS), the most common form of dysautonomia, may be associated with autoimmunity in some cases. Autoantibodies against the ganglionic acetylcholine receptor (gAChR) have been reported in a minority of patients with POTS, but the prevalence and clinical relevance is unclear.MethodsClinical information and serum samples were systematically collected from participants with POTS and healthy control volunteers (n = 294). The level of positive gAChR antibodies was classified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…These three patients all had low levels of gAChR antibodies (<0.12 nmol/L). The lack of association between gAChR antibodies and POTS was also seen in a study of POTS patients in the community, which detected seropositivity in only 7% of patients, a figure comparable to that found in healthy controls [ 29 ]. Taken together, these findings suggest that gAChR antibodies are rarely elevated in POTS patients and are unlikely to be a relevant marker for distinguishing between subtypes of POTS.…”
Section: Discussionmentioning
confidence: 57%
“…These three patients all had low levels of gAChR antibodies (<0.12 nmol/L). The lack of association between gAChR antibodies and POTS was also seen in a study of POTS patients in the community, which detected seropositivity in only 7% of patients, a figure comparable to that found in healthy controls [ 29 ]. Taken together, these findings suggest that gAChR antibodies are rarely elevated in POTS patients and are unlikely to be a relevant marker for distinguishing between subtypes of POTS.…”
Section: Discussionmentioning
confidence: 57%
“…8 A number of studies have explored this area by studying the prevalence and activity of autoantibodies against cardiovascular G protein-coupled receptors (GPCRs) in patients with POTS. 7,[9][10][11][12][13][14][15] Some studies have found increased concentrations of GPCR autoantibodies, as well as a variety of others, in patients with POTS. 10,11 Despite this extensive research, there is no consensus as to what role autoantibodies against GPCRs and other receptors play in the pathophysiology of POTS.…”
mentioning
confidence: 99%
“…In addition, autoantibodies have been found in healthy controls as well as in patients. 15 Most studies of GPCR autoantibodies in POTS have had small samples sizes and have lacked appropriate internal controls. 16 Using a relatively large multicenter cohort, we sought to test the null hypothesis that GPCR autoantibody concentrations are not different between patients with POTS and healthy controls using an established, commercially available enzyme-linked immunosorbent assay (ELISA).…”
mentioning
confidence: 99%
“…In clinical practice, 30-50% of patients with AAG have a high antibody titer. However, lower titer of α3-nAChR antibodies might be present in other autonomic syndromes including postural tachycardia syndrome [8], peripheral autonomic neuropathies, and more localized forms of autonomic impairment such as pure gastrointestinal motility failure. The clinical relevance of the α3-nAChR antibodies at low titer is unclear.…”
Section: Doctor What About These Antibody Results?mentioning
confidence: 99%